2011
DOI: 10.1200/jco.2010.32.0994
|View full text |Cite
|
Sign up to set email alerts
|

Progression From High-Grade Prostatic Intraepithelial Neoplasia to Cancer: A Randomized Trial of Combination Vitamin-E, Soy, and Selenium

Abstract: This trial does not support the hypothesis that combination vitamin E, selenium, and soy prevents progression from HGPIN to PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 22 publications
4
48
2
Order By: Relevance
“…Similar to this study, selenium, lycopene and soy have also not shown to reduce the risk of prostate cancer 1 2. However, the findings of the present study are inconsistent with two other contemporary studies.…”
Section: Commentarycontrasting
confidence: 59%
“…Similar to this study, selenium, lycopene and soy have also not shown to reduce the risk of prostate cancer 1 2. However, the findings of the present study are inconsistent with two other contemporary studies.…”
Section: Commentarycontrasting
confidence: 59%
“…Other randomized studies have shown no benefit to dietary supplementation with selenium, lycopene, or soy in reducing the risk of risk of invasive cancer in men with high-grade prostatic intraepithelial neoplasia (HGPIN) on biopsy. 13,14 In this report we detail an observation of serious public health concern that has emerged with continued follow-up of SELECT participants. With primary endpoint ascertainment based on contemporary community practice across the US, Canada, and Puerto Rico using PSA and DRE as indications for biopsy, the risk of prostate cancer at 7 years of median follow-up was increased by 17% in men randomized to supplementation with vitamin E alone a difference which started to appear about two years post randomization.…”
Section: Commentmentioning
confidence: 99%
“…Other randomized studies have shown no benefit to dietary supplementation with selenium, lycopene, or soy in reducing the risk of risk of invasive cancer in men with high- grade prostatic intraepithelial neoplasia (HGPIN) on biopsy. 13,14 …”
Section: Commentmentioning
confidence: 99%